COVID-19 Vaccination and Mental Health: A Difference-In-Difference Analysis of the Understanding America Study - Koltai, Jonathan; Raifman, Julia; Bor, Jacob; McKee, Martin; Stuckler, David (American journal of preventive medicine, 2022)
Mental health problems increased during the COVID-19 pandemic. The knowledge that one is less at risk after being vaccinated may alleviate distress, but this hypothesis remains unexplored. This study tests whether psychological distress declined in those vaccinated against COVID-19 in the U.S. and whether changes in anticipatory fears mediated any association. A nationally representative cohort of U.S. adults (N=8,090) in the Understanding America Study were interviewed regularly from March 2020 to June 2021 (28 waves). Difference-in-differences regression tested whether vaccination reduced distress (Patient Health Questionnaire 4 scores), with mediation analysis used to identify potential mechanisms, including perceived risks of infection, hospitalization, and death. Vaccination was associated with a 0.04-SD decline in distress (95% CI= −0.07, −0.02). Vaccination was associated with a 7.77–percentage point reduction in perceived risk of infection (95% CI= −8.62, −6.92), a 6.91-point reduction in perceived risk of hospitalization (95% CI= −7.72, −6.10), and a 4.68-point reduction in perceived risk of death (95% CI= −5.32, −4.04). Including risk perceptions decreased the vaccination–distress association by 25%. Event study models suggest that vaccinated and never vaccinated respondents followed similar Patient Health Questionnaire 4 trends before vaccination, diverging significantly after vaccination. Analyses were robust to individual and wave fixed effects and time-varying controls. The effect of vaccination on distress varied by race/ethnicity, with the largest declines observed among American Indian and Alaska Native individuals (β= −0.20, p<0.05, 95% CI= −0.36, −0.03). COVID-19 vaccination was associated with declines in distress and perceived risks of infection, hospitalization, and death. Vaccination campaigns could promote these additional benefits of receiving the COVID-19 vaccine.